Object categorization of Chinese-English bilinguals in a free response task. - Marliana Mohamed Aron. (2009)
This study examined three types of object relationships – taxonomic, thematic and classifier – in spontaneous thoughts of Chinese-English bilinguals. We employed an open-ended response task and recruited fifty-three Chinese-English bilinguals to test the following predictions: 1) bilinguals who were tested in Chinese would be more likely to use the Chinese classifier system as a basis for categorization than those who were tested in English, 2) thematic object relationship would be used more often than the other two relationships to categorize objects regardless of language, and 3) descriptions of thematic object relationship were more likely to involve contextual information. We found support for the second and third hypothesis – providing evidence that thematic relation is universal and the most accessible in everyday thoughts. We then further discussed the connection of bilinguals’ languages with the way objects are associated.